PENGARUH MODEL PEMBELAJARAN ACTIVE LEARNING TIPE LEARNING START WITH A QUESTION DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA SMAN 2 BAYANG - Ayu Antiti; Marwan Usman (Jurnal Kajian Pendidikan Ekonomi, 2015)
This research is to show the influence of Active Learning model of Learning Start with a Question and Learning Motivation toward the students’ Economic Achievement of grade X at SMAN 2 Bayang.This research is included as quasi-experiment research. The population is students of grade 10thof SMAN 2 Bayang of year of 2014-2015. By using purposing sampling technique, the students in 10.6 (Control classroom) and the students of 10.5 (experiment classroom) are taken as the sample. Data analysis technique is descriptive analysis, inductive analysis and hypothesis testing using T-test analysis and two-way Anova. The findings of the research are (1) the students’ Economic Achievement who have been taught by using Active Learning model Start With A Question learning type is higher than the students who have been taught  by using Conventional teaching model. (2) The high motivated students who have been taught by using Active Learning model Start With A Question learning type have higher Economic Achievement than  those  who have been taught by using Conventional teaching model. (3) The low motivated students who have been  taught by using  Active Learning model Start With A Question learning type have higher Economic Achievement than those who have been taught  by using Conventional teaching model. (4) there is no interaction between the teaching strategy Active Learning Start With A Question learning model and motivation toward the students’ Economic Achievement. Based on this research, it is suggested to the Economic teacher to use active learning model type learning start with a question in order to improve students ability.